Sprache der Transzendenzerfahrungen Die Briefsammlung der Parapsychologischen Beratungsstelle in Freiburg i.B. - Hofer, Janina Maris (Religionswissenschaft, 2018)
The relation between language and transcendental experiences has been newly defined in a qualitative exploration of paranormal experiences.